Using infographics as a technology-based tool to develop 21st century skills in an ESL context - Fetylyana Nor Pazilah; Harwati Hashim (Global Econedu, 2018)
Technology is advancing every day and there is no stopping to it. It plays a vital role in our daily lives which includes in education field. The use of technology is massively implemented in classrooms as teaching strategies. Old teaching strategies such as visual aids are often improvised to match with the students’ interest. Teachers would usually find it difficult to teach students who are digital natives and demand a much more familiar and casual learning environment. It is also significant for teachers to equip the students with all 21st century skills in an ESL classroom. The students would prefer if the teachers could teach using any technological tools. Infographics is one of the visual aids that integrates the use of technology. Online application such as Easel.ly can be used to strengthen teaching and learning sessions. Hence, this paper reviewed on the effectiveness of using infographics in developing 21st century skills in an ESL context.